ACTIVATION AND PURIFICATION OF BENTONITE FOR THE TREATMENT OF CRUDE PALM OILAS VEGETABLE OIL - Tutun Nugraha; Yestine Yuliantina; Supandi Suminta (Jurnal Sains Materi Indonesia, 2011)
ACTIVATION AND PURIFICATION OF BENTONITE FOR THE TREATMENT OF CRUDE PALM OILAS VEGETABLE OIL. Crude Palm Oil (CPO) to be used for cooking oil requires processing that includes bleaching step which is typically done using bleaching earth made from activated bentonite. Bentonite is a type of mineral that is very rich in montmorillonite. Currently, substantial amount of activated bentonite used by vegetable oil industries are imported. In this research, the bentonite was obtained locally from the region of Leuwiliang (Bogor, West Java). The bentonite was purified using solution of sodium-hexa-metaphosphate (NaPO3)6, and was activated using acid reflux methods (H2SO4, 100 oC). The bentonite activation was done at two different reflux times (1 and 3 hour), and three different acid concentrations (1 M, 2.5 M and 5 M). To assist the interpretation of results, the bentonite samples were also studied using XRF and XRD. Bleaching power of active bentonite was initially studied using adsorption of methylene blue for optimation, which was followed by bleaching of CPO. The results showed that, the purified bentonite and activated at 1 molar H2SO4 for 1 hour duration, had the highest bleaching capacity. In addition, the treated oil also showed substantial reduction of peroxide number, and also some reduction of free fatty acid content (FFA) which further improve the quality treated palm oil.